Participation in paralympic sports: What it means to female student-athletes with disabilities - Mohamad Diah, Nurazzura; Abd Rahim, Badruel Hairiel (Atlantis Press, 2019)
Women’s involvement in sports continues to evolve over the years. This scenario has affected their socialization process and altered their life expectations. This paper examines the non-sport factors of sports participation among female student-athletes with disabilities in Kuala Lumpur, Malaysia. Ten participants (N=10) were recruited using the purposive sampling technique. All participants were female student-athletes with disabilities, aged between 13-17 years old, from the Malay, Chinese and Indian ethnic group. They have competed in goalball, para-athletics and para-swimming. All data were analysed using thematic analysis. Results of this study show: i) sport is considered a mechanism to achieve different life goals, ii) sport is an avenue to express their emotions and iii) civic identity is promoted through their participation in sports. In short, sport is vital in the life of female student-athletes with disabilities as it empowers them to be their best and makes them feel good about themselves.